Studi Komparatif: Pengaruh Model Problem Based Learning dan Direct Instruction Terhadap Sikap Ilmiah Siswa pada Materi GLB Dan GLBB di Kelas XI IPA (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Abstract This study aims to analyze the comparative effect of Problem Based Learning (PBL) and Direct Instruction (DI) models on students' scientific attitudes on the material of Uniform Straight Motion (GLB) and Uniformly Accelerated Straight Motion (GLBB) in Class XI Science. The study used a quasi-experimental method with a Nonequivalent Control Group Design involving two sample classes, namely the experimental class (XI F6, n = 21) which was taught with the PBL model and the control class (XI F5, n = 17) which was taught with the DI model. The research instrument was a 30-item scientific attitude questionnaire whose validity and reliability had been tested. Data were analyzed using an inferential statistical test of independent samples t-test at a significance level of α = 0.05. The results of the study showed that there was a significant difference between the scientific attitudes of the group of students taught with the PBL model and the group of students taught with the DI model (p-value = 0.006 < 0.05), with the average scientific attitude score of the PBL group (126.81 ± 8.92) significantly higher than the DI group (119.35 ± 7.45). The conclusion of the study proved that the Problem Based Learning model was more effective in improving students' scientific attitudes on GLB and GLBB materials compared to the Direct Instruction model, so it is recommended for physics teachers to implement the PBL model as an innovative learning alternative to optimize the formation of students' scientific character.